Effects of space environment temperature on the mechanical properties of carbon fiber/bismaleimide composites laminates. (January 2018) - Yang, Baifeng; Yue, Zhufeng; Geng, Xiaoliang; Wang, Peiyan; Gan, Jian; Liao, Baohua
The effects of space environment temperatures on specific carbon fiber/bismaleimide composite laminates were evaluated using the simulated environment test method. The tests were performed at −120 ℃, room temperature, 150 ℃, 170 ℃, and 200 ℃. The material responses were characterized through an assessment of mechanical properties including tensile, compressive, and in-plane shear properties. The experimental results showed that transverse tensile/compressive and in-plane shear responses, which are strongly related to matrix properties, were sensitive to temperature especially high temperature above the glass transition temperature. Failure morphologies on both the microscopic and macroscopic scales were discussed. It was found that matrix fracture and delamination was more likely at high temperatures, while the interface strength was higher at low temperatures. The effects of extreme temperatures on mechanical responses of composites, as well as dynamic thermomechanical analysis results, are shown. Failure envelopes for these carbon fiber / bismaleimide composites at different temperatures based on Hashin criteria are depicted to help designers to avoid drawbacks introduced by temperature.